Molecular detection of Borrelia sp. in Ornithodoros cavernicolous (Acari: Argasidae) in midwestern Brazil - Mayara Garcia Polli; Maria Marlene Martins; Vinicius da Silva Rodrigues; Lais Miguel Rezende; Adriane Suzin; Rodrigo da Costa Maia; Ana Carolina Prado Souza; Sebastián Muñoz-Leal; Matias Pablo Juan Szabó; Jonny Yokosawa (Ticks and Tick-Borne Diseases, 2024)
Ticks are obligate hematophagous parasites that can transmit to vertebrate hosts several pathogens, including viruses, bacteria, protozoa and helminths. Among these agents, some Borrelia species some Borrelia species cause disease in humans and other vertebrate hosts; therefore, they have medical and veterinary health importance. To gather additional information on Borrelia species in Brazil, the current study aimed to detect the presence of these species in Ornithodoros cavernicolous ticks collected in September 2019 from cement pipes that are used by bats as shelter in a farm located in the midwestern region of Brazil. DNA samples obtained from 18 specimens of O. cavernicolous were subjected of two polymerase chain reactions, targeting a segment of the Borrelia fla B gene. Of the samples tested, only one (6 %, 1/18) showed amplification. The nucleotide sequence of the amplified DNA showed more than 97 % (293/300) identity with a sequence of a Borrelia sp. detected in blood collected from a bat from Macaregua Cave, Colombia, and more than 97 % (292/300) detected in lungs from vampire bats from northeastern Brazil. The deduced amino acid sequences were identical to each other. Phylogenetic analysis indicated that these sequences formed a group of Borrelia species (putatively associated with bats) that is closely related to sequences of Borrelia species of the Lyme borreliosis group. Further investigations should be carried out in order to determine whether the sequence of the Borrelia sp. we found belongs to a new taxon. It will also be of great importance to determine which vertebrate hosts, besides bats, O. cavernicolous ticks can parasitize in order to investigate whether the Borrelia sp. we found may be transmitted and cause disease to the other vertebrate hosts.